Translating linguistic innovation in Francophone African novels - Woodham, Kathryn (2007)
Ortega y Gasset's assertion that 'to write well is to make continual incursions into grammar, into established usage, and into accepted linguistic norms' finds resonance in the work of a number of sub-Saharan Francophone African writers, most notably in texts by Ahmadou Kourouma, Veronique Tadjo, Werewere Liking, Henri Lopes and Sony Labou Tansi. The types of incursions that are most characteristic of these authors include the incorporation of visible and quasi-invisible traces of African languages, the exploitation of stylistic features associated with orality, including sustained use of colloquialisms and vulgarisms, and experimentation with various kinds of wordplay.